Core-shell particles for simultaneous three-dimensional imaging and tweezing in dense colloidal materials - Dullens, R; Liu, Y; Edmond, K; Curran, A; Bryant, C; Peng, B; Aarts, D; Sacanna, S (Wiley, 2016)
Colloidal suspensions of microspheres have been used as idealized yet accurate physical models of complex phase behaviours for over a century. Moving beyond simple observations, researchers have begun to probe colloidal materials directly by manipulating individual particles using optical tweezers. However, simultaneous optical manipulation and 3D visualisation of dense colloidal samples poses significant technical challenges due to their conflicting requirements: while 3D visualisation requires optical transparency, optical tweezing and manipulation requires a refractive index contrast between the ‘probe’ particles and solvent.